Three‐Dimensional Distribution of Bone‐Resorption Lesions in Osteonecrosis of the Femoral Head Based on the Three‐Pillar Classification. Issue 7 (29th September 2021) - Liu, Guang‐bo; Lu, Qiang; Meng, Hao‐ye; Quan, Qi; Zhang, Yu‐xuan; Li, Huo; Ma, Hai‐yang; Zhao, Jun; Wang, Peng; Zhou, Xue‐feng; Peng, Jiang
Abstract : Objective: To investigate three‐dimensional distribution of bone‐resorptive lesions based on the three‐pillar classification and its effect on the disease progression of osteonecrosis of the femoral head (ONFH). Methods: A total of 194 femoral head CT images from 117 patients diagnosed with ARCO stage II and III ONFH were retrospectively reviewed from April 2014 to February 2019. Three‐dimensional structures of the femoral head and the bone‐resorptive lesions were reconstructed. Using the three‐pillar classification and coronal plane of the femoral head, we divided each femoral head into six regions to observe the location characteristics of bone‐resorption lesions, and explore the destruction of different areas of the femoral head by the bone‐resorptive lesions. Then the hips were divided into two groups based on whether they contained bone‐resorption lesions and compared the difference of stage II and stage III between the two groups. Results: The regional distribution revealed 39 (27.27%), 55 (38.46%), six (4.20%), 23 (16.08%), 17 (11.89%) and three (2.10%) bone‐resorptive lesions in regions I, II, III, IV, V and VI respectively. The lateral pillar, AL (I + IV), contained 44.76% of the lesions, central pillar, C (II + V), 48.95%, and medial pillar, M (III + VI), 6.29%. Moreover, there were 81.82% bone‐resorption lesions in anterolateral pillar, AL (I + II + IV), and 18.18% in posteromedial pillar, PM (III + V + VI). In all ONFH hips, the lateral pillar of 81(88.04%) femoral heads were affected, the central pillar of 84 (91.30%) femoral heads were affected, and the medical pillar of 29 (31.52%) femoral heads were affected. The ratio of ARCO stage III in the group with bone‐resorption lesions was significantly higher than that of the group without bone‐resorption lesions (76.09% vs 30.39%, P < 0.001). Conclusions: This study demonstrated that the bone‐resorption lesions are mainly distributed in the lateral and central pillar of the femoral head, and the two pillars of the femoral head are usually involved by bone‐resorption lesions. Furthermore, the ratio of ARCO stage III in the group with bone‐resorption lesions was significantly higher than that of the group without bone‐resorption lesions, suggesting that the bone‐resorption lesions might accelerate the progression of ONFH. Abstract : The bone‐resorption lesions are mainly distributed in the lateral, central pillar of the femoral head, and the lateral and central pillar of the femoral head with bone‐resorption lesions is usually involved. Furthermore, the result suggested that the bone‐resorption lesions might accelerate the progression of ONFH.